2015
DOI: 10.1016/j.erss.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale hydropower in Africa: Socio-technical designs for renewable energy in Tanzanian villages

Abstract: a b s t r a c tIn this article, we explore the process of economic change following the NGO-led implementation of a small-scale off-grid hydropower system in Tanzania. We examine how the implementing actor deals with economic challenges and local ownership in order to achieve sustainable electricity supply. The qualitative case study shows that the NGO, ACRA-CCS, has overcome a number of constraints, which are sometimes associated with donor funding. This has been achieved by having multiple donors, an integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 39 publications
1
67
0
Order By: Relevance
“…(For a similar approach focusing on micro-hydropower in Tanzania, see [15].) This cluster of theories provide a useful perspective for examining the dynamic interaction between people and technology at various levels, including the way end-users contribute to the innovation of socio-technological systems such as village-level solar power supply.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
See 1 more Smart Citation
“…(For a similar approach focusing on micro-hydropower in Tanzania, see [15].) This cluster of theories provide a useful perspective for examining the dynamic interaction between people and technology at various levels, including the way end-users contribute to the innovation of socio-technological systems such as village-level solar power supply.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…The CBO membership elects a 12-member board with gender balance and geographical balance. 15 Six members from this board then form the executive committee responsible for overseeing the management of the energy center.…”
Section: Institutional and Operational Designmentioning
confidence: 99%
“…On the other hand, recent studies have shown successful renewable energy adoption when a research team works directly with the local population to ensure their full participation in decision-making. For example, in this Special Issue, Ahlborg and Sjöstedt [41] conducted a case study on a hydropower in Tanzania and Ulsrud et al [42] on a solar project in Kenya.…”
Section: Socio-technical Systems In Energy Researchmentioning
confidence: 99%
“…Sustainable electricity pricing for Tanzania lead to important cost advantages for power generation. Other development-oriented initiatives, backed by development organizations, are rooted in community development which actively enhance the productive use of electricity, which include not only generation but also local distribution (Ahlborg & Sjöstedt, 2015).…”
Section: Investment Via Small Power Producersmentioning
confidence: 99%